FAKOR-FAKTOR YANG BERHUBUNGAN DENGAN KESIAPAN MITIGASI KEBAKARAN PADA POM BENSIN MINI (Studi di Kecamatan Banyumanik dan Tembalang Kota - Khoirotun Nisak; Bina Kurniawan; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
A mini gas station was place to sell retail fuel oil (BBM) using a manual pump equipment with storage tube and digital calculations. Safety standards at mini gas stations were not really good yet. There were mini gas stations that did not have fire extinguishers (APAR) or traditional fire extinguishers arround the mini gas station area. There was an incident of fire in mini gas station that was located in Kudus which burned the owner's house and one person was injured. This study was to analyze factors related to fire mitigation readiness at a mini gas station. It was quantitative research by using a cross-sectional study. The population in this study were 20 mini gas station workers. The sample that was used was total sampling technique with 20 respondents. Data collected by questionnaire consist of questions and observations. The statistical analysis used was chi-square test. Based on result variable that related to fire mitigation readiness were years of work(p-value = 0.020), knowledge (p-value = 0.005), application of work procedures (p-value = 0.005). While variables that were not related to fire mitigation readiness were age (p-value = 0.628), gender (p-value = 1,000), education level (p-value = 0.582), and work motivation (p-value = 0.057). Suggestions that could be applied at mini gas stations were increase knowledge and hold training through coaching directly from owners or providers to improve skills workers in fire mitigation.